Assessment of the benefit of achieving complete versus almost complete skin clearance in psoriasis: a patient's perspective. (17th February 2022) - Korman, Neil J.; Malatestinic, William; Goldblum, Orin M.; Murage, Mwangi J.; Renda, Lisa; Lin, Chen-Yen; Lucas, James; Middleton, Chloe; Lobosco, Steven
Abstract: Background: Psoriasis is characterized by thick and scaly plaques. The Dermatology Life Quality Index (DLQI) and Physician Global Assessment (PGA) can be used to define its severity. Objective: To assess the impact of complete clearance of skin versus almost clear skin across various disease measures. Methods: Data were collected in a survey of US dermatologists and patients with psoriasis from November 2016–January 2017. Dermatologists completed a 6-point PGA (0 = clear skin, 1 = almost clear skin). Patients completed the DLQI and Work Productivity and Activity Impairment questionnaire (WPAI). Patients with clear and almost clear skin were compared using analysis of covariance for continuous variables, and multivariate logistic regression analysis for categorical variables. Results: Data for 99 and 160 patients with clear and almost clear skin, respectively, were included in the analyses. Patients with clear skin reported less frequent and lower intensity itching, lower total DLQI score (indicating better health-related quality of life), and less impairment of overall work productivity than patients with almost clear skin (all: p < 0.05). Limitations: Limitations relating to general survey methodology. Conclusion: Patients perceived a meaningful difference between clear and almost clear skin. Clear skin is now a realistic treatment target with newer biologics approved in psoriasis.